Letter from Joseph Hodges to Linda Berg - Joseph W. Hodges, Jr.:::::: (1974)
A letter from Joseph Hodges, the City Manager for Oxnard, to Linda Berg discussing the procedure for appointing citizens to various committees or commissions.